Design and fabricate multipurpose desk for student - Muhammad Zamri, Azmi (2008)
Designing and fabrication a multipurpose desk for student is a product that fulfills the students needs. This project uses many materials such as zinc, hollow steel bar and others. Overall, this project involves many processes, starting from the design concept, fabrication and assembling procedures. Even though there are many types of multipurpose desk for student in the market, the completion of this new model provides a more practical usage.